New Hope for Resistant Hypertention - Rahman, Z; Karmaker, KK; Ahmed, M; Aziz, M; Chowdhury, S; Datta, B (Cardiovascular Journal, 2012)
Hypertension is a major public health problem. Despite the increasing awareness of hypertension and its implications among patients and treating physicians, the prevalence of resistant hypertension remains high. Resistant hypertension define as blood pressure that remains elevated above treatment goals despite administration of an optimal three drug regimen that include a diuretic1 The prevalence of resistant hypertension is projected to increase, owing to the aging population and increasing trends in obesity, sleep apnea, and chronic kidney disease. It is estimated that at least 10% of all patients with hypertension are resistant to existing drugs. Management of resistant hypertension must begin with a careful evaluation of the patient to confirm the diagnosis and exclude factors associated with pseudo-resistance, such as improper BP measurement technique, the white-coat effect, and poor patient adherence to life-style and/or antihypertensive medications. Despite the use of the appropriate dose and type of diuretic to overcome the management of resistant hypertension, we cant achieve our goal. But there is at least two devices namely Baroreflex Activation Therapy and Catheter-based renal sympathetic denervation make the new hope for the patient with resistant hypertension DOI: http://dx.doi.org/10.3329/cardio.v5i1.12278 Cardiovasc. j. 2012; 5(1): 81-91